Effectivenessof Child Health Monitoring System in Simomulyo PHC Surabaya - Prima Dian Kartika Sari (Jurnal Berkala Epidemiologi, 2017)
The number of infant deaths in the Public health center (PHC) of Simomulyo reached 16 infant deaths in 2015 and 12 infant deaths in 2016. This study aims to evaluate the effectiveness of the child health monitoring system at the PHC of Simomulyo based on a system approach (input, process, output). This research is an evaluative descriptive study with the informants of the research are the Village Midwife, the Midwife Coordinator, and the Midwife Holder of the Children's Health Services Program at the PHC of Simomulyo, Surabaya. The results of this study indicate that the input variables which include data types and data sources have been implemented effectively. Evaluation of the effectiveness of process variables in the compilation of data has been carried out effectively, data collection, cohort data tracking, and making follow-up plans, implemented quite effectively, and gap analysis carried out less effectively. Evaluation of the effectiveness of output variables in the calculation of service coverage is less effective. The conclusion of this study is that the effectiveness of the implementation of process components and outputs in Local Area Monitoring - Mother and Child Health. Child health indicators at the PHC of Simomulyo are classified as less effective. Alternative solutions offered by researchers are socialization and workshops to all program holders and village midwives, utilizing a uniform reporting format in conducting gap analysis, tracking cohort data, and preparing follow-up plans.